2019
DOI: 10.3201/eid2508.181432
|View full text |Cite
|
Sign up to set email alerts
|

17DD Yellow Fever Revaccination and Heightened Long-Term Immunity in Populations of Disease-Endemic Areas, Brazil

Abstract: We evaluated the duration of neutralizing antibodies and the status of 17DD vaccine–specific T- and B-cell memory following primary and revaccination regimens for yellow fever (YF) in Brazil. We observed progressive decline of plaque-reduction neutralization test (PRNT) seropositivity and of the levels of effector memory CD4+ and CD8+ T cells, as well as interferon-γ+CD8+ T cells, 10 years after primary vaccination. Revaccination restored PRNT seropositivity as well as the levels of effector memory CD4+, CD8+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
3
40
0
1
Order By: Relevance
“…Some studies that investigated the impact of booster doses on the status of YF-specific immune response in adults postulated that booster vaccination did not increase the titers of YF-specific antibodies nor induced or altered the phenotypes of CD8 + T-cells and the immune responses observed following revaccination were reduced compared to primary responses (23, 29, 30). However, other studies have demonstrated that booster doses are relevant to guarantee the long-term persistence of 17DD-YF-specific memory components in travelers (31) and in residents of areas with YF-virus circulation (32, 33). Therefore, the single dose recommendations for YF vaccines have been considered controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies that investigated the impact of booster doses on the status of YF-specific immune response in adults postulated that booster vaccination did not increase the titers of YF-specific antibodies nor induced or altered the phenotypes of CD8 + T-cells and the immune responses observed following revaccination were reduced compared to primary responses (23, 29, 30). However, other studies have demonstrated that booster doses are relevant to guarantee the long-term persistence of 17DD-YF-specific memory components in travelers (31) and in residents of areas with YF-virus circulation (32, 33). Therefore, the single dose recommendations for YF vaccines have been considered controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that evaluated the timeline kinetics of correlates of protection after 17D-YF and 17DD-YF vaccination in adults have demonstrated that both humoral and cellular-mediated YF-specific immunity display a relevant decline overtime in single dose recipients of YF vaccines and that the booster doses efficiently improve the immunological status in re-vaccinated recipients (2933). Recent studies from our group have shown that secondary or multiple vaccination regimens in adults are able to further improve the immunity parameters triggered by primary 17DD-YF vaccination and restore the resultant YF-specific memory in 100% of the volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The live attenuated YFV vaccine (17DD) is one of the most efficient vaccines ever developed, providing long-lasting immunity that wanes about 10 years after vaccination. Revaccination can rescue the 17DD-specific long-term immunity [59]. Both innate and adaptive immune responses are elicited by the 17DD vaccination, while nAbs have been defined as the best correlations of protection against this viral infection.…”
Section: Yellow Fevermentioning
confidence: 99%
“…While IgM antibodies can persist after YF immunization, it is unknown if there is similar endurance after natural infection [44]. Neutralizing antibodies, which primarily consist of IgG antibodies, can remain for many years after immunization and natural infection, and can confer protection against re-infection [45][46][47][48]. There are no documented cases of repeated YFV infection, even in several historical cohorts [49].…”
Section: Introductionmentioning
confidence: 99%